2021
DOI: 10.1089/apc.2021.0008
|View full text |Cite
|
Sign up to set email alerts
|

Examining How Health Navigation Affects Mental Health Among Gay, Bisexual, and Other Men Who Have Sex with Men Living with Human Immunodeficiency Virus in Guatemala

Abstract: Gay, bisexual, and other men who have sex with men (GBMSM) are disproportionately affected by mental health problems and human immunodeficiency virus (HIV). Health navigation has the potential to improve both HIV and mental health outcomes; however, few studies have measured the impact of navigation on mental health among people living with HIV. We analyzed longitudinal data from a sociobehavioral survey and navigation monitoring system with GBMSM living with HIV in Guatemala (n = 346) that participated in a 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Consistente con métodos cualitativos, es decir, los resultados hallados no son generalizables a todo usuario con VIH, pero son similares a lo encontrado, por ejemplo, en otros estudios sobre programas de navegación con HG en Guatemala y con poblaciones de origen latino en EE. UU que incluían HG y MT (32,33) . Los usuarios que se entrevistaron para el presente estudio estaban vinculados a la atención médica, por lo que no tenemos evidencia de las percepciones de HSH y MT que no se vincularon o abandonaron el cuidado.…”
Section: Discussionunclassified
“…Consistente con métodos cualitativos, es decir, los resultados hallados no son generalizables a todo usuario con VIH, pero son similares a lo encontrado, por ejemplo, en otros estudios sobre programas de navegación con HG en Guatemala y con poblaciones de origen latino en EE. UU que incluían HG y MT (32,33) . Los usuarios que se entrevistaron para el presente estudio estaban vinculados a la atención médica, por lo que no tenemos evidencia de las percepciones de HSH y MT que no se vincularon o abandonaron el cuidado.…”
Section: Discussionunclassified
“…Similar results were reported by a health navigator intervention among MSM in Guatemala, which also found that clients who required more support from navigators and external sources experienced worse HIV and mental health outcomes. 57 Additional research is needed to determine if and how integrated HIV and behavioral health services can ensure that individuals who are referred to external services receive the support they need to achieve and maintain viral suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Navigation interactions occurred in person, through phone conversations, and through virtual texting/chatting. Additional details of the navigation component are described elsewhere (Alvis-Estrada et al, 2021; Davis, Angeles, et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…We used monitoring data from the study psychologist and the navigation monitoring system to create measures of intervention participation (Alvis-Estrada et al, 2021; Davis, Angeles, et al, 2021).…”
Section: Methodsmentioning
confidence: 99%